2022
DOI: 10.1038/s41467-022-30062-8
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of 1015 patients’ exomes reveals genomic-clinical associations in colorectal cancer

Abstract: The genetic basis of colorectal cancer (CRC) and its clinical associations remain poorly understood due to limited samples or targeted genes in current studies. Here, we perform ultradeep whole-exome sequencing on 1015 patients with CRC as part of the ChangKang Project. We identify 46 high-confident significantly mutated genes, 8 of which mutate in 14.9% of patients: LYST, DAPK1, CR2, KIF16B, NPIPB15, SYTL2, ZNF91, and KIAA0586. With an unsupervised clustering algorithm, we propose a subtyping strategy that cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“…Using our panel of 95 cancerassociated genes, we found that the mutational burden varied greatly among patients (0-237 mutations), with an average of 7 mutations per patient. This data is consistent with the reported wide range of tumor mutational burden in CRC and also suggested that some hypermutated cases in our cohort could have microsatellite instability (23).…”
Section: Discussionsupporting
confidence: 93%
“…Using our panel of 95 cancerassociated genes, we found that the mutational burden varied greatly among patients (0-237 mutations), with an average of 7 mutations per patient. This data is consistent with the reported wide range of tumor mutational burden in CRC and also suggested that some hypermutated cases in our cohort could have microsatellite instability (23).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we found that genomic alterations overall provided inferior performance compared to the panel of methylation markers, and importantly, our attempt to integrate the mutation profile with the methylation markers showed marginal enhancement. The mutational landscape of human genome identified in stool DNA was highly consistent with what has been known for Chinese CRC patients 52 , which suggests that these mutant genomes indeed came from malignant colorectal epithelial cells and mutational profile of fecal DNA may be used effectively as non-invasive markers for CRC. Nevertheless, our results showed that mutational status as diagnostic markers provided high specificity (near 100%) but sensitivity was suboptimal.…”
Section: Discussionsupporting
confidence: 70%
“…The captured mtDNA libraries were sequenced on Illumina HiSeqXTen (Illumina) platform using paired-end (PE) of 150 bp. For cohort 2, the detailed protocol for library construction and whole exome sequencing (WES) with the WESplus gene panel, which is an upgraded version of the standard WES and can capture mitochondrial DNA (HaploX Biotechnology, Shenzhen, China), has been previously described 27 . The sequencing in cohort 2 was performed on NovaSeq 6000 platform (Illumina) using PE 150.…”
Section: Methodsmentioning
confidence: 99%